The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s12903-020-01321-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to dental care access among asylum seekers and refugees in highly developed countries: a systematic review

Abstract: Background Dental diseases are prevalent among asylum seekers and refugees (ASRs). Despite significant treatment needs, access to dental care in host countries is often limited. The aim of this systematic review was to identify the barriers and enablers to dental care access for ASRs in host countries of very high development. Methods Five health and social care databases and eight grey literature sources of information were searched. The Critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(92 citation statements)
references
References 36 publications
(100 reference statements)
6
86
0
Order By: Relevance
“…Through the results of this study, nationality and the origin of the patient seemed to play a signi cant role in the oral health status, as patients from Afghanistan and Syria seemed to have signi cantly higher DMFT average value compared to other nationalities, the explanation of this result need further investigation and data collection as many factors can determine the oral health status like socioeconomic status, the trends and tradition regarding oral health hygiene, and the length of the route taken to reach Europe (8, 15, 25, 28), the result of our study agrees with another research which found signi cant difference in oral health between refugees from middle east compared to refugees from Africa, as refugees from middle east had worse oral health status (29), and the previous research explained this result because of the different diet as the African diet is low in fat and sugar, and the habit of brushing teeth, for example, tooth-brushing was a daily habits for all African participants in the previous study (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…Through the results of this study, nationality and the origin of the patient seemed to play a signi cant role in the oral health status, as patients from Afghanistan and Syria seemed to have signi cantly higher DMFT average value compared to other nationalities, the explanation of this result need further investigation and data collection as many factors can determine the oral health status like socioeconomic status, the trends and tradition regarding oral health hygiene, and the length of the route taken to reach Europe (8, 15, 25, 28), the result of our study agrees with another research which found signi cant difference in oral health between refugees from middle east compared to refugees from Africa, as refugees from middle east had worse oral health status (29), and the previous research explained this result because of the different diet as the African diet is low in fat and sugar, and the habit of brushing teeth, for example, tooth-brushing was a daily habits for all African participants in the previous study (29,30).…”
Section: Discussionsupporting
confidence: 92%
“…Through the results of this study, nationality and the origin of the patient seemed to play a signi cant role in the oral health status, as patients from Afghanistan and Syria seemed to have signi cantly higher DMFT average value compared to other nationalities, the explanation of this result need further investigation and data collection as many factors can determine the oral health status like socioeconomic status, the trends and tradition regarding oral health hygiene, and the length of the route taken to reach Europe (8,15,25,28), the result of our study agrees with another research which found signi cant difference in oral health between refugees from middle east compared to refugees from Africa, as refugees from middle east had worse oral health status (29), and the previous research explained this result because of the different diet as the African diet is low in fat and sugar, and the habit of brushing teeth, for example, tooth-brushing was a daily habits for all African participants in the previous study (29,30).…”
Section: Demographic Data and Sample Analysissupporting
confidence: 92%
“…As shown in Appendix 3, other key issues and challenges include transportation, an unfamiliar healthcare system, a lack of trust in the services and a limited understanding of how the system works, healthcare coverage and cost, time pressures associated with visiting healthcare centres, a lack of social support, employment obligations, and no continuity of care. Anxiety relating to medical treatment and particular health beliefs can also become problematic (Paisi et al, 2020). Furthermore, healthcare service frameworks for "good practice" are important to improve refugee access, equity and the quality of care as well as planning and evaluating services (Feldman, 2006).…”
Section: Theme 1: Refugee Access and Adaptation To Healthcare Service...mentioning
confidence: 99%